Data protection and privacy : data protection and artificial intelligence - Computers, Privacy and Data Protection (Conference) 2020 : Brussels, Belgium); Hallinan, Dara; Leenes, Ronald; Hert, Paul de (Gordonsville : Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This book brings together papers that offer conceptual analyses, highlight issues, propose solutions, and discuss practices regarding privacy, data protection and Artificial Intelligence. It is one of the results of the thirteenth annual International Conference on Computers, Privacy and Data Protection (CPDP) held in Brussels in January 2020. The development and deployment of Artificial Intelligence promises significant break-throughs in how humans use data and information to understand and interact with the world. The technology, however, also raises significant concerns. In particular, concerns are raised as to how Artificial Intelligence will impact fundamental rights. This interdisciplinary book has been written at a time when the scale and impact of data processing on society - on individuals as well as on social systems - is becoming ever starker. It discusses open issues as well as daring and prospective approaches and is an insightful resource for readers with an interest in computers, privacy and data protection"--
Interim Table of Contents -- 1. Don't accept candy from strangers: An analysis of third-party mobile SDKs lvaro Feal, Julien Gamba, Juan Tapiador, Primal Wijesekera, Joel Reardon, Serge Egelman and Narseo Vallina-Rodriguez -- 2. AI and the Right to Explanation: Three Legal Bases under the GDPR Tiago Cabral -- 3. A Comparison of Data Protection Regulations for Automotive Systems Ala'A Al-Momani, Christoph Bösch and Frank Kargl -- 4. Misaligned Union laws? A comparative analysis of certification in the Cybersecurity Act and the General Data Protection Regulation Irene Kamara -- 5. Aggregation, synthesization and anonymization: a call for a risk-based assessment of anonymization approaches Sophie Stalla-Bourdillon and Alfred Rossi -- 6. The role of the EU fundamental right to data protection in an Algorithmic and Big data world Yordanka Ivanova -- 7. Implementing AI in Healthcare: An Ethical and Legal Analysis Based on Case Studies Eduard Fosch Villaronga, Davit Chokoshvili, Vibeke Binz Vallevik, Marcello Ienca and Robin L Pierce -- 8. Technological Experimentation without Adequate Safeguards? Interoperable EU Databases and Access to the Multiple Identity Detector by SIRENE Bureaux Diana Dimitrova and Teresa Quintel.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Data protection -- Law and legislation -- Congresses; Privacy, Right of -- Congresses; Artificial intelligence -- Law and legislation -- Congresses; IT & Communications law; Electronic books